Pengaruh Kebijakan Utang dan Pertumbuhan Penjualan terhadap Profitabilitas Perusahaan dengan Kebijakan Dividen sebagai Variabel Moderasi - Tasiman Tasiman; Reskino Reskino (Universitas Jember, 2024)
This research examines business profitability and debt policy as well as sales growth, using dividend policy as a moderator. All employees of the business are studied. By using dividend policy as a moderator, this research explores how debt policy and sales growth affect company profitability. The LQ 45 Company on the Indonesian Stock Exchange was studied from 2020 to 2022. This research used Saturated Sampling, that is, taking a sample of the entire population. Testing shows that Debt Policy is detrimental to the company's profitability. Sales Growth increases Company Profitability, according to testing. In this test, dividend policy does not moderate the relationship between debt policy and business profitability. Dividend policy moderates the effect of Sales Growth on company profitability, according to test results. Keywords: Debt Policy, Sales Growth, Profitability, Dividend Policy